Attitudes of Greek EFL teachers towards MALL: a phenomenographic study - Kefala, Eirini (Language Center, Cyprus University of Technology, 2020)
Mobile-Assisted Language Learning (MALL) is one of the recent trends in the field of language learning, and teachers should be able to access as many resources as possible in order to stay up-to-date. Continuing Professional Development programmes (CPDs) such as master degrees, national and international certificates/seminars or PhDs are some of the ways teachers can keep up with the latest trends in every scientific field. This dissertation intends to explore the range attitudes of the Greek EFL teachers towards MALL-related practices and their needs regarding professional development. The phenomenographic approach is adopted as it can richly describe the object of study by emphasising the variation in the meaning that is found in the participants’ experiences of the phenomenon; in this case, the range of perceptions of attitudes of the Greek EFL teachers towards MALL. Phenomenography is defined as an interpretative approach with an interest to explore the qualitative variation in people’s experience of aspects of the world around them (Bruce, 1999). Semi-structured online interviews with 15 Greek EFL teachers were carried out, in order to discover and analyse the various fluctuations regarding the opinions, experiences and visions, existing in the population of the Greek EFL teachers towards MALL. The findings showed that the majority of the Greek EFL teachers have positive attitudes towards the integration of MALL in the EFL classes, although they indicate that there are no MALL-related EFL CPDs organised locally
Keywords: EFL; Greek EFL teachers; MALL; CPD; Phenomenography